Just knowing those two points we can come up with an equation.

Firstly, we know h and k (at the vertex):

(h, k) = (1,1)

So let's put that into this form of the equation:

f(x) = a(x-h)^{2} + k

f(x) = a(x-1)^{2} + 1

Then we calculate "a":

And so here is the resulting Quadratic Equation:

f(x) = 0.5(x-1)^{2} + 1

wrong

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up